Diagnostic Accuracy of Electrochemical Skin Conductance in the Detection of Sudomotor Fiber Loss - Porubcin, Michal G.; Novak, Peter (Frontiers in Neurology, 2020)
Background: Small fiber neuropathy (SFN) is a common health problem. SFN is associated with loss of small fibers, either sensory, autonomic or both. Reduced autonomic sudomotor sweat gland nerve fiber density (SGNFD) and sensory epidermal nerve fiber density (ENFD) can be seen in SFN. Electrochemical skin conductance (ESC) is a noninvasive test for measurement of sudomotor function. This study evaluated the diagnostic accuracy of ESC to detect abnormal SGNFD and ENFD. Methods: This was a retrospective blinded study of participants referred for evaluation of SFN. The primary outcome measure was the specificity and sensitivity of ESC to diagnose loss of small fibers using SGNFD and ENFD as reference tests. The secondary outcome measures were the correlation between ESC and neuropathy severity, pain and autonomic clinical scales. Results: 210 patients were enrolled in the study, age (mean±sd) 45.5±16.1 years, men/women=52/158. ESC adjusted for weight (ESC/kg) was reduced in subjects with abnormally low SGNFD (normal/abnormal, ESC/kg=1.19±0.31/0.94±0.37 μSiemens/kg, p <0.0001) and abnormally low ENFD (normal/abnormal ESC/kg 1.20±0.37/1.04±0.33 μSiemens/kg, p<0.0011). ESC/kg correlated with SGNFD (ρ=0.39, p<0.0001) and ENFD (ρ=0.47, p<0.0001). ESC/kg did not correlate with symptom scales. ESC/kg had 64% sensitivity and 77% specificity (ROC 0.73, p=0.0001) to predict abnormal SGNFD and 69% sensitivity and 55% specificity (ROC 0.63, p=0.0017) to predict abnormal ENFD. In comparison, SGNFD had 50.1% sensitivity and 85.1% specificity to predict abnormal ENFD (ROC 0.69, p=0.0001). Conclusion: ESC/kg has modest accuracy to detect SGNFD loss. ESC may be a useful test in characterization of small fiber neuropathy.